Strategic Management of Strengthening Religious Moderation Setting of Cultural Acculturations in Pancasila Kampung - Utomo, Tri Prasetiyo; Muchklisin, Nur (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Gaprang Village Subdistrict Kanigoro Regency Blitar get nickname of Pancasila village. Giving the nickname of Pancasila village is based on existence three religions; Islam, Christianity and Hinduism. There is no multi-religion in Pancasila village cause dispute, but become character unique tied in harmony life multicultural. Form harmony is immortalized in A building masgapur, acronym from Mosques, Churches, and Temples. Research This aiming take a picture management strategic actions taken religious figures for strengthening moderation religious acculturation setting culture . Research methods use qualitative descriptive. Research results show; 1) formulation of strengthening strategies moderation religious done through preservation culture wisdom local as acculturation culture. 2) Implementation of strategy through carnival culture, development gate masgapur (Mosque, Church, and Temple). 3) Acculturation culture become settings strengthening moderation religion in the Pancasila village of Gaprang Village Regency Blitar.